Indigenous Movements, Self-Representation, and the State in Latin America - Jackson, Jean E. (Jean Elizabeth), 1943-; Warren, Kay B., 1947- (Book collections on Project MUSE., 2002)
Throughout Latin America, indigenous peoples are responding to state violence and pro-democracy social movements by asserting their rights to a greater measure of cultural autonomy and self-determination. This volume's case studies of movements in Colombia, Guatemala, and Brazil weigh the degree of success achieved by indigenous leaders in influencing national agendas when governments display highly ambivalent attitudes about strengthening ethnic diversity. The contributors to this volume are anthropologists and indigenous activists from the United States and Latin America. They address the double binds of indigenous organizing and "working within the system" as well as the flexibility of political tactics used to achieve cultural goals outside the scope of state politics. The contributors answer questions about who speaks for indigenous communities, how indigenous movements relate to the popular left, and how conflicts between the national indigenous leadership and local communities play out in specific cultural and political contexts. The volume sheds new light on the realities of asymmetrical power relations and on the ways in which indigenous communities and their representatives employ Western constructions of subjectivity, alterity, and authentic versus counterfeit identity, as well as how they manipulate bureaucratic structures, international organizations, and the mass media to advance goals that involve distinctive visions of an indigenous future